(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This research looks at how HR and marketing work together to develop corporate branding strategy and increase workers’ roles as brand ambassadors. A structured questionnaire was used to gather primary data from 120 workers as part of a descriptive study design. Secondary materials, including research publications and organizational reports, were consulted for support. About 75% of workers are eager to serve as brand ambassadors, according to the data, which show that integrated HR-marketing initiatives greatly increase employee engagement, motivation, and advocacy. Structured staff training, campaign participation, incentive and recognition schemes, open internal communication, and leadership backing are important components of a successful partnership. According to the report, integrating marketing and HR initiatives improves employee happiness, organizational loyalty, and brand visibility in addition to strengthening employer branding. In today’s cutthroat economic climate, these insights provide firms useful suggestions for using staff members as brand ambassadors.